Urticaria and other mimickers of urticaria - María Isabel Rojo-Gutierrez; Carol-Vivian Moncayo-Coello; Carol-Vivian Moncayo-Coello; Alejandra Macias Weinmann; Rene Maximiliano Gomez; Luis Felipe Ensina; Ivan Cherrez-Ojeda; Ivan Cherrez-Ojeda; Pedro Piraino Sosa; Patricia Latour Staffeid; Marylin Valentin Rostan (Frontiers in Allergy)
Urticaria is a mast cell-dependent skin disease characterized by the presence of hives, angioedema, or both in the absence of systemic symptoms. It may be acute, or chronic. (1) Acute urticaria (AU) is common in children, affecting boys and girls equally. Chronic urticaria (CU) affects adult women more (3). AU affects more than 20% of the population and CU 0.1 and 1.5%. There are many pathologies that do not meet the clinical criteria for urticaria, despite being called urticarias, which leads to erroneous diagnoses and inconclusive epidemiology. This review attempts to clarify when we should consider urticaria as such and what are the diagnoses that can be considered urticaria without being so.